Antithrombocytopenic and immunomodulatory potential of metabolically characterized aqueous extract of Carica papaya leaves - Varisha Anjum; Poonam Arora; Shahid Husain Ansari; Abul Kalam Najmi; Sayeed Ahmad (Taylor & Francis Group, 2017)
Context: Carica papaya Linn. (Caricaceae) leaf (CPL) juice has long been traditionally used in ethnomedicine for dengue fever. Objective: The study examines the effects of standardized CPL aqueous extract (SCPLE) on platelet count, extramedullary haematopoiesis (EMH), and immunomodulation in cyclophosphamide (CP)-induced animal model of thrombocytopenia. Materials and methods: The extract was analyzed for myricetin, caffeic acid, trans-ferulic acid, and kaempferol using HPTLC for standardization followed by UPLC-qTOF/MS fingerprinting for metabolite signature. The effects of SCPLE (50 and 150 mg/kg p.o.) on proliferative response of platelet count and total leucocyte count (TLC) were observed up to 14 days in Wistar rat. However, delayed-type hypersensitivity (DTH), haemagglutination titre (HT), and in vivo carbon clearance were examined as immunomodulatory parameters in albino mice at 150 mg/kg p.o. against CP. Results: The quantitative HPTLC estimation of SCPLE showed the presence of myricetin, caffeic acid, trans-ferulic acid, and kaempferol up to 280.16 ± 5.99, 370.18 ± 6.27, 1110.86 ± 2.97, and 160.53 ± 2.48 (μg/g), respectively. Twenty-four metabolites were identified using UPLC-qTOF/MS. Oral administration of SCPLE (150 mg/kg) in thrombocytopenic rats exhibited significant (p < 0.01) increase in thrombocytes (1014.83 × 103 cells/mm3), DTH response (0.16 ± 0.004), and phagocytic index (63.15% increase) as compared to CP-induced thrombocytopenia group. Histopathological studies showed minimal fibrosis in spleen histology. Discussion and conclusions: Results suggest CPL can mediate the release of platelets providing the means for the treatment and prevention of dengue.